Pengaruh Suplementasi Vitamin D terhadap Overall Survival dan Progression-Free Survival pada Pasien Kanker Kolorektal - Widyartini, Ni Wayan Eka; Eka Andayani, Diyah (Jurnal Ilmu Kesehatan Indonesia, 2025)
Background: Colorectal cancer (CRC) is the fourth most common cancer and the fifth leading cause of cancer death in Indonesia. Despite treatment advances, prognosis remains poor, with high recurrence rates and low long-term survival. Vitamin D has recently emerged as a potential adjunct due to its role in modulating tumor progression and improving survival outcomes. Objective: To evaluate the effect of vitamin D supplementation on overall survival (OS) and progression-free survival (PFS) in patients with colorectal cancer. Methods: A structured literature search was conducted using PubMed, Cochrane Library, and Google Scholar, focusing on studies published between 2020 and 2025. Eligible studies included randomized controlled trials (RCTs), systematic reviews, and meta-analyses involving adult CRC patients receiving vitamin D supplementation. Articles were appraised using the Oxford Centre for Evidence-Based Medicine (CEBM) criteria. Results: Two meta-analyses studies met the inclusion criteria. The meta- analyses by Vaughan-Shaw et al. demonstrated a significant improvement in PFS (HR = 0.65) with vitamin D supplementation, particularly at a dose of 4,000 IU/day for 23 months in metastatic CRC patients. Whereas the meta-analyses by Xu et al. reported inconsistent findings, primarily based on observational data with unclear dosing. Major limitations included small sample sizes, heterogeneous populations, and inconsistent reporting of outcomes and dosages. Conclusion: High-dose vitamin D supplementation may improve progression-free survival in colorectal cancer. However, stronger evidence from large, well-designed trials is needed to confirm its effectiveness and inform clinical practice.